A32 DEVELOPMENT AND VALIDATION OF THE TORONTO UPPER GASTROINTESTINAL CLEANING SCORE. (21st February 2022) - Seleq, S; Khan, R; Gimpaya, N; Vargas, J I; Amin, S; Bilal, M; Bollipo, S; Charabaty, A; de-Madaria, E; Hashim, A; Kral, J; Pawlak, K M; et al.
Abstract: Background: High quality esophagogastroduodenoscopy (EGD) depends on the ability to appropriately visualize upper gastrointestinal (GI) mucosa pathology. Evaluation can be limited by the presence of mucus, foam, bubbles and solid materials. Currently, there is no standardized method to assess mucosal visualization for use in clinical or research settings. Aims: To develop and establish the content validity of the Toronto Upper Gastrointestinal Cleaning Score (TUGCS) and evaluate its interrater reliability. Methods: An international panel of endoscopy experts rated potential items and their associated anchors for importance as indicators of adequacy of mucosal visualization during EGD. The survey utilized a Likert scale (1 (strongly disagree) to 5 (strongly agree)). The Delphi process was repeated until consensus was reached. Consensus was defined priori as ≥80% of experts in a given round scoring ≥4 on all survey items. To assess content validity, 48 EGD procedures were evaluated in real-time by two endoscopist reviewers using the TUGCS at a single institution. The interrater agreement between assessments was calculated for TUGCS total scores using intraclass correlation coefficient, one-way random effects model (ICC 1, 1). Results: Fourteen experts agreed to be part of the Delphi panel. An anatomical framework representing the upper GI mucosa and anchors for each mucosal portion representing various levels of visibility was generated through systematic review. Three survey rounds, with response rates of 100%, 100% and 71% respectively, achieved consensus. The final TUGCS includes four anatomical areas (fundus, body, antrum, duodenum) and mucosal visualization anchors ranging from 0 to 3 (Figure 1). TUGCS was used to assess foregut cleaning in 48 procedures (Table 1). The mean TUGCS for staff and trainee were 8.1 (±2.4) and 8.1 (±2.6), respectively. The ICC was 0.78 (95% confidence interval 0.62–0.88) indicating good reliability. Conclusions: We developed and generated content validity evidence for the TUGCS through rigorous Delphi methodology, reflective of practice across different centres. Planned as future research is a video survey distributed to endoscopists internationally to further validate the TUGCS to create a tool that may be used to judge mucosal visualization for EGD in research and clinical settings. Funding Agencies: None